2012
DOI: 10.1002/ana.23570
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐permeable AMPA receptors are expressed in a rodent model of status epilepticus

Abstract: Objective To characterize the plasticity of AMPA receptor (AMPAR)-mediated neurotransmission in the hippocampus during status epilepticus (SE). Methods SE was induced by pilocarpine and animals were studied after 10 min (refractory-SE) or 60 min (late-SE) of the first grade V seizures. AMPAR-mediated currents were recorded from CA1 pyramidal neurons and dentate granule cells (DGCs) by voltage-clamp technique. The surface expression of GluA2 subunit on hippocampal membranes was determined using a biotinylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 136 publications
(160 citation statements)
references
References 51 publications
4
155
0
1
Order By: Relevance
“…GluA2-lacking AMPA receptors are calcium permeable and may contribute to calcium accumulation, possibly leading to neuronal death [48]. These findings indicate a role for glutamate receptor antagonists in status epilepticus, and, in particular, NMDA receptor antagonists as a means of modifying the condition (possibly preventing drug resistance).…”
Section: Other Changesmentioning
confidence: 92%
See 2 more Smart Citations
“…GluA2-lacking AMPA receptors are calcium permeable and may contribute to calcium accumulation, possibly leading to neuronal death [48]. These findings indicate a role for glutamate receptor antagonists in status epilepticus, and, in particular, NMDA receptor antagonists as a means of modifying the condition (possibly preventing drug resistance).…”
Section: Other Changesmentioning
confidence: 92%
“…receptor and GABA(B) receptor expression is decreased, and AMPA receptors lose their GluA2 subunit [25,[47][48][49]. GluA2-lacking AMPA receptors are calcium permeable and may contribute to calcium accumulation, possibly leading to neuronal death [48].…”
Section: Other Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending these findings, herein we hypothesize that AMPAR-mediated excitatory conductance is progressively enhanced during ESE. To test this hypothesis, SE was induced in lithium-pretreated adult male rats using pilocarpine, and the animals were studied either 10 min (early ESE) or 60 min (late ESE) after the onset of the first grade V behavioral seizure using a combination of electrophysiological and biochemical studies as described previously (Rajasekaran et al, 2012;Kozhemyakin et al, 2013).AMPAR-mediated excitatory postsynaptic currents (EPSCs) were recorded from CA1 pyramidal neurons (CA1-PNs) and dentate granule cells (DGCs) by voltageclamp technique. Analysis of recordings obtained from CA1-PNs revealed that the frequency of action-potential independent EPSCs (m-EPSCs) increased with increasing seizure duration (p < 0.0001, one-way analysis of variance [ANOVA]).…”
mentioning
confidence: 99%
“…TTA-P2 (10 mg/ kg; supplied by Dr. Victor Uebele at Merck), 0.05 mg/kg MK 801, and/or 20 mg/kg GYKI 52466 (cf. Rajasekaran et al 2012) were administered via i.p. injections prior to EEG and behavior recording.…”
Section: Eeg Recording and Behavior Monitoringmentioning
confidence: 99%